Can stride kinematics help explain differences in running economy in Triathletes? - D'auria, S.; Manning, J.; Moss, S.; Granthan, J. (National Elite Sports Council 2009 Athlete Services Forum - High Performance Programming for Success - 11-12th November - Satellite Program - Applied Physiology Conference 2009 - Australian Institute of Sport, Canberra - 10th, 11th and 13th November, 2009)
Run performance is influenced by several factors, with one of the strongest relationships being with running economy. Improvements to running economy are likely to positively affect performance. Running economy is often described by the relative oxygen consumption at descrete velocities and is routinely measured in laboratory treadmill step tests. One factor thought to affected running economy is stride kinematics i.e. ground contact time, flight time and the resulting stride rate and length. Methods Routine laboratory testing in accordance with Australian Triathlon test protocols (4-5, 4min sub maximal efforts with 1 minute rest between each effort followed by a 30 second type rapid ramp to exhaustion) was carried out on 10 elite Junior and Under 23 athletes. Test set up consisted of AEI Moxus metabolic cart, Payne Wide Body Treadmill, Lactate Pro, Polar HR, OptoJump light sheet. Data from the 10 athletes was analysed for relationships between running economy and stride kinematics. Results Data will be presented on "possible" relationships between treadmill running economy and stride kinematics. Discussion/Conclusion The potential utility of considering stride kinematics when trying to account for differences in treadmill running economy will be discussed with respect to the current data set as will the technology utilised to collect the kinematics data.